Principles and practice of public administration in Nigeria - Adebayo, Augustus (Ibadan: Spectrum Book Limited, 1994)
This book combines the theory and practice of administration, and applies it to the daily experience and function of government in Nigeria.
Includes bibliographical references and index.
osc 06/09/2016
Loans
Keywords: Public Administration; Civil service; Nigeria $1 (BPolitics and government.s; Nigeria